Cancer Stem Cells in Neuroblastoma: Expanding the Therapeutic Frontier - Bahmad, Hisham F.; Chamaa, Farah; Assi, Sahar; Chalhoub, Reda M.; Abou-Antoun, Tamara; Abou-Kheir, Wassim (Frontiers in Molecular Neuroscience, 2019)
Neuroblastoma (NB) is the most common extracranial solid tumor often diagnosed in childhood. Despite intense efforts to develop a successful treatment, current available therapies are still challenged by high rates of resistance, recurrence and progression, most notably in advanced cases and highly malignant tumors. Emerging evidence proposes that this might be due to a subpopulation of cancer stem cells (CSCs) or tumor-initiating cells (TICs) found in the bulk of the tumor. Therefore, the development of more targeted therapy is highly dependent on the identification of the molecular signatures and genetic aberrations characteristic to this subpopulation of cells. This review aims at providing an overview of the key molecular players involved in NB CSCs and focuses on the experimental evidence from NB cell lines, patient-derived xenografts and primary tumors. It also provides some novel approaches of targeting multiple drivers governing the stemness of CSCs to achieve better anti-tumor effects than the currently used therapeutic agents.